Jamaica : Third Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2014)
This paper presents Jamaica's Third Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria report. The IMF staff report highlights that recent data is in-line with GDP growth of some 1 percent in 2013-2014. Inflation has increased since 2012 due to the depreciation of the exchange rate as well as higher administered prices, but has moderated in recent months. The policy agenda under the program is now shifting to reforms in several areas including tax and customs administration, public financial management, securities dealers, the framework for monetary policy, and the business environment.